Ursodeoxycholic acid dissolution of gallstones in cystic fibrosis. Issue 6 (June 1988) - Salh, B; Howat, J; Webb, K
Abstract : The dissolution of cholesterol gall stones is documented in two adults with cystic fibrosis.